SCAR: Scrap Book based on Culturally Responsive Teaching Enriched with Augmented Reality - Yuniawatika Yuniawatika; Maytha Esterya Lumban Gaol; Ika Feny Nur Aini; Lailatul Fitriah; Edwin Maulana Sandya (JINoP (Jurnal Inovasi Pembelajaran), 2025)
Cultural diversity in the material of practicing the 3rd principle of Pancasila can introduce cultural diversity, foster an attitude of tolerance, and respect from an early age. However, the lack of variations in learning media makes it difficult for students to understand the diversity of Indonesian culture, and they tend to be passive in learning. Based on the results of observations and interviews that have been conducted, it shows that there are obstacles experienced by teachers in developing media and using learning methods. Limited time, energy, and resources make it difficult for teachers to create varied learning media. This study aims to develop valid and engaging learning media by integrating the Culturally Responsive Teaching approach and Augmented Reality technology to improve students' understanding of cultural diversity. The research and development (R&D) method is applied in this research, which applies the ASSURE model. The validation results from media experts obtained 90%, material experts 85%, and teachers 94%. If interpreted, all three are included in the category of very valid. While the results of the attractiveness test on a small scale obtained a percentage of 93.75% and a large scale of 98%, both are included in the very attractive category if interpreted. So it can be concluded that SCAR: Scrap Book based on Culturally Responsive Teaching Enriched with Augmented Reality is worth using.